A circular RNA circ-DNMT1 enhances breast cancer progression by activating autophagy. Issue 44 (1st November 2018) - Du, William; Yang, Weining; Li, Xiangmin; Awan, Faryal; Yang, Zhenguo; Fang, Ling; Lyu, Juanjuan; Li, Feiya; Peng, Chun; Krylov, Sergey; Xie, Yizhen; Zhang, Yaou; et al.
Abstract Circular RNAs are a large group of noncoding RNAs that are widely expressed in mammalian cells. Genome-wide analyses have revealed abundant and evolutionarily conserved circular RNAs across species, which suggest specific physiological roles of these species. Using a microarray approach, we detected increased expression of a circular RNA circ-Dnmt1 in eight breast cancer cell lines and in patients with breast carcinoma. Silencing circ-Dnmt1 inhibited cell proliferation and survival. Ectopic circ-Dnmt1 increased the proliferative and survival capacities of breast cancer cells by stimulating cellular autophagy. We found that circ-Dnmt1-mediated autophagy was essential in inhibiting cellular senescence and increasing tumor xenograft growth. We further found that ectopically expressed circ-Dnmt1 could interact with both p53 and AUF1, promoting the nuclear translocation of both proteins. Nuclear translocation of p53 induced cellular autophagy while AUF1 nuclear translocation reduced Dnmt1 mRNA instability, resulting in increased Dnmt1 translation. From here, functional Dnmt1 could then translocate into the nucleus, inhibiting p53 transcription. Computational algorithms revealed that both p53 and AUF1 could bind to different regions of circ-Dnmt1 RNA. Our results showed that the highly expressed circular RNA circ-Dnmt1 could bind to and regulate oncogenic proteins in breast cancer cells. Thus circ-Dnmt1 appears to be an oncogenic circular RNA with potential for further preclinical research.